Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To determine the inverse of the function [tex]\( f(x) = \frac{x}{4} - 2 \)[/tex], let's follow these steps:
1. Rewrite the function:
[tex]\[ y = \frac{x}{4} - 2 \][/tex]
Here, we're expressing [tex]\( f(x) \)[/tex] as [tex]\( y \)[/tex].
2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ x = \frac{y}{4} - 2 \][/tex]
This step reflects the definition of the inverse function, where the input [tex]\( x \)[/tex] of the original function becomes the output of the inverse function [tex]\( f^{-1}(x) \)[/tex], and vice versa.
3. Solve for [tex]\( y \)[/tex]:
- First, isolate [tex]\( \frac{y}{4} \)[/tex]:
[tex]\[ x + 2 = \frac{y}{4} \][/tex]
- Then, multiply both sides by 4 to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 4(x + 2) \][/tex]
4. Express the inverse function:
[tex]\[ f^{-1}(x) = 4(x + 2) \][/tex]
So the inverse of the function [tex]\( f(x) = \frac{x}{4} - 2 \)[/tex] is:
[tex]\[ f^{-1}(x) = 4(x + 2) \][/tex]
Thus, the correct answer is [tex]\( \boxed{4(x + 2)} \)[/tex].
To verify, let's check which option matches our result:
- A. [tex]\( f^{-1}(x) = 4(x-2) \)[/tex] (No match)
- B. [tex]\( f^{-1}(x) = 4(x+2) \)[/tex] (Match)
- C. [tex]\( f^{-1}(x) = 2(x-4) \)[/tex] (No match)
- D. [tex]\( f^{-1}(x) = 2(x+4) \)[/tex] (No match)
Based on our calculations, option B [tex]\( (4(x + 2)) \)[/tex] is the correct inverse function of [tex]\( f(x) = \frac{x}{4} - 2 \)[/tex].
1. Rewrite the function:
[tex]\[ y = \frac{x}{4} - 2 \][/tex]
Here, we're expressing [tex]\( f(x) \)[/tex] as [tex]\( y \)[/tex].
2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ x = \frac{y}{4} - 2 \][/tex]
This step reflects the definition of the inverse function, where the input [tex]\( x \)[/tex] of the original function becomes the output of the inverse function [tex]\( f^{-1}(x) \)[/tex], and vice versa.
3. Solve for [tex]\( y \)[/tex]:
- First, isolate [tex]\( \frac{y}{4} \)[/tex]:
[tex]\[ x + 2 = \frac{y}{4} \][/tex]
- Then, multiply both sides by 4 to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 4(x + 2) \][/tex]
4. Express the inverse function:
[tex]\[ f^{-1}(x) = 4(x + 2) \][/tex]
So the inverse of the function [tex]\( f(x) = \frac{x}{4} - 2 \)[/tex] is:
[tex]\[ f^{-1}(x) = 4(x + 2) \][/tex]
Thus, the correct answer is [tex]\( \boxed{4(x + 2)} \)[/tex].
To verify, let's check which option matches our result:
- A. [tex]\( f^{-1}(x) = 4(x-2) \)[/tex] (No match)
- B. [tex]\( f^{-1}(x) = 4(x+2) \)[/tex] (Match)
- C. [tex]\( f^{-1}(x) = 2(x-4) \)[/tex] (No match)
- D. [tex]\( f^{-1}(x) = 2(x+4) \)[/tex] (No match)
Based on our calculations, option B [tex]\( (4(x + 2)) \)[/tex] is the correct inverse function of [tex]\( f(x) = \frac{x}{4} - 2 \)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.